ANALISIS KUALITAS FINAL PROYEK WEBSITE MILIK BANK BOYOLALI TERHADAP PENGGUNA AKHIR(METODE WEBQUAL 4.0) - Sony Cahyo Wibisono; Amir Hamzah; Uning Lestari (Jurnal Jarkom, 2015)
website development focuses only on the system, interface and content of the website content without any satisfaction research on the website is presented, this study aims to determine the level of satisfaction of the end user as well as an evaluation before the website was published on the main domain, research methods used WebQual 4.0 and scale linkert as the study interval. WebQual is one method or technique of measuring the quality of a website based on the perception of the end user. 4.0 WebQual method is based on three dimensions of usability, information quality dimensions and dimensional quality of the interaction. In the process of analysis used tranches respondent sample of 100 people consisting of 82 respondents which includes customers and employees as well as the 18 respondents not clients, data collection is divided into 50 respondents using an online questionnaire and 50 respondents using offline questionnaires. The next stage is the analysis of data consisting of validity, reliability and assessment with linkert scale. On the validity of the test using the formula Pearson Bevariate while test reliability using Cronbach's alpha formula. In the assessment using linkert scale with 5 scale interval. Based on the results of the research, the average total value sufficient satisfaction for publicizing the website with some items of the dimensions of quality of interaction that must be repaired.